2001
DOI: 10.2202/0027-6014.1161
|View full text |Cite
|
Sign up to set email alerts
|

Two Measures of the Diversity of the Labor Pool for Entry-Level Student Affairs Positions

Abstract: This study investigated the demographic diversity of the labor pool for entry-level professional positions in student affairs. Two sources were used: the data maintained by the National Center for Education Statistics on degrees conferred in fields related to student affairs, and an e-mail survey of preparation programs listed in the NASPA and ACPA on-line directories. Overall, women were found to comprise 67%–68% of the labor pool for entry-level positions; African Americans: 12%–15%; Hispanics: 4%–5%; Asian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The majority of students enrolled in this diversity class each semester are female, White, Christian, heterosexual, and between the ages of 23-28. 3 These demographics, namely being predominantly White and female, are reflective of the population of students enrolled in student affairs professional preparation programs; they are demographically fairly homogeneous (Rapp, 1997;Tull, 2006;Turrentine & Conley, 2001). Rachel, the student who serves as an illustrative case of multicultural competence for social justice, is a White, heterosexual female, in her midtwenties.…”
Section: Rachel: An Illustrative Casementioning
confidence: 99%
“…The majority of students enrolled in this diversity class each semester are female, White, Christian, heterosexual, and between the ages of 23-28. 3 These demographics, namely being predominantly White and female, are reflective of the population of students enrolled in student affairs professional preparation programs; they are demographically fairly homogeneous (Rapp, 1997;Tull, 2006;Turrentine & Conley, 2001). Rachel, the student who serves as an illustrative case of multicultural competence for social justice, is a White, heterosexual female, in her midtwenties.…”
Section: Rachel: An Illustrative Casementioning
confidence: 99%
“…Despite the attention given by the profession to the problem, inequities in staffing patterns continue to appear in the professional literature (Bensimon, 2004; Turrentine & Conley, 2001). Researchers have found that there is inadequate representation by staff members of color (Hurtado et al, 2008; Turner, Myers, & Creswell, 1999), and that women, though present in the profession in growing numbers, are underrepresented in senior level positions (Reason, Walker, & Robinson, 2002; Turner, Gonzalez, & Wong, 2011; Turner, Gonzalez, & Wood, 2008).…”
mentioning
confidence: 99%
“…Staff members, in this case, in nonmanagerial job positions, are mostly ignored. Additionally, women employed in non-managerial, entry-level positions in higher education are overrepresented, as such jobs require minimal experience (Turrentine & Conley, 2001). Considering the overrepresentation of women in nonmanagerial job positions, Turrentine and Conley (2001) stated that women are underrepresented in administrative and senior-level management positions.…”
Section: Human Resources Developmentmentioning
confidence: 99%
“…Additionally, women employed in non-managerial, entry-level positions in higher education are overrepresented, as such jobs require minimal experience (Turrentine & Conley, 2001). Considering the overrepresentation of women in nonmanagerial job positions, Turrentine and Conley (2001) stated that women are underrepresented in administrative and senior-level management positions. The literature proves that in addition to the issues experienced by African American/Black women employed in non-managerial positions, there is a diversity, equity, and inclusion issue with promotion and retention practices at PWIs.…”
Section: Human Resources Developmentmentioning
confidence: 99%